Speaking for the People : Native Writing and the Question of Political Form - Rifkin, Mark, 1974- (Book collections on Project MUSE., 2021)
"Mark Rifkin examines nineteenth-century Native writings by William Apess, Elias Boudinot, Sarah Winnemucca, and Zitkala-Ša to rethink and reframe contemporary debates around recognition, refusal, and resurgence for Indigenous peoples."--